Better than sex: further development and validation of the consumption gender scale. Issue 3 (2nd March 2020) - Pohlmann, Attila; Chen, Qimei
Abstract : Purpose: Biological sex is an important segmenting variable in marketing. Yet its ability to meaningfully distinguish beyond the female/male dichotomy is limited. With traditional gender roles continuously shifting and contemporary fluid conceptualizations of gender altering the consumption mainstream, the diverse and multi-faceted behaviours related to gender elude market segment distinctions that are based on biological sex alone. Thus far, researchers have had only limited success applying the concept of gender identity and gender schema theory to inform marketing research and management. The purpose of this study is to further develop a consumer decision-oriented scale that addresses this gap by providing a more sensitive method of segmentation. Design/methodology/approach: The scale was validated according to common psychological scale development techniques. Findings: Not only does the Consumption Gender Scale predict the behaviours and media preferences of traditional, gender-schematic male and female consumer segments, but it also accounts for the variance in the behaviours of gender-aschematic non-traditional men and women. We demonstrate the scale's predictive power in two experimental studies and discuss its potential to serve as an intermediary variable that can predict product attitudes and purchase intentions on social media. Research limitations/implications: The Consumption Gender Scale was based on surveys and experiments conducted in the USA. Future research could examine the suitability of the scale in other cultural contexts. Practical implications: The Consumption Gender Scale provides a finer taxonomy for organizations to use in segmenting their target market on the basis of consumption-relevant gender rather than biological sex. Consequently, it also provides opportunities for managers to fine-tune their media-planning efforts. Originality/value: Biological sex as the main segmenting variable has become inadequate because of ongoing shifts in gender roles and changes in associated consumption behaviours. To address the shortcomings of traditional methods, we advocate for and validate a continuous measurement scale.